The association between maternal serum first trimester free βhCG, second trimester intact hCG levels and foetal growth restriction and preeclampsia. (3rd April 2018) - Sharony, Reuven; Sharon-Weiner, Maya; Kidron, Debora; Sukenik-Halevy, Rivka; Biron-Shental, Tal; Manor, Mira; Reinstein, Eyal; Maymon, Ron
Abstract: The purpose of this study was to analyse the association between free beta hCG (fβhCG) increased levels and pregnancy complications (PC), foetal growth restriction (FGR) and preeclampsia (PE). This connection was evaluated in two stages (i) investigating the association between those PC with first trimester fβhCG and second trimester intact hCG (ihCG), and (ii) studying the association between these two analytes in the same pregnancy. This was a retrospective study in two settings: medical centre that provided data on fβhCG and ihCG levels in pregnancies with FGR and PE, and central laboratory that provided fβhCG and ihCG levels that were compared in the same pregnancy. No association was found between those PC and the hCG analytes, except for elevated ihCG levels and FGR. Elevated fβhCG (>3.00 MoM) was found in 570/16, 849 (3.4%) women. However, only 14% of whom had elevated second trimester ihCG. A positive correlation was found between the magnitude of first trimester fβhCG levels and the percentage of women who had elevated second trimester ihCG. This association was determined by the magnitude of the elevation of fβhCG levels. Impact statement: What is already known on this subject: The two analytes, first trimester fβhCG and second trimester ihCG, are independently produced and parameters of the biochemical screening during pregnancy. What the results of this study add: Referring to 3.00 MoM as cut-off levels, most pregnancies with elevated levels of first trimester fβhCG will have normal ihCG second trimester levels. What the implications are of these findings for clinical practice and/or further research: The risk of developing pregnancy complications, FGR and PE should be associated with second trimester ihCG levels. About 3.5% of women had high fβhCG levels during the first trimester. However, only 14% also had increased ihCG levels, defined as >3.00 MoM; additional studies are needed to explore the association between increased first trimester fβhCG levels and the risk of developing pregnancy complications, independent of ihCG levels in the second trimester.